2016
DOI: 10.1002/jsfa.7540
|View full text |Cite
|
Sign up to set email alerts
|

Extraction methods of Amaranthus sp. grain oil isolation

Abstract: The results of this study indicate that it is very important to choose both the right genotype and the right method of extraction for optimal oil and squalene yield. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 50 publications
2
34
0
Order By: Relevance
“…Generally, ScCO 2 is a recommended technique for nonpolar compound extraction with molecular weights less than 500 g/mol soluble in CO 2 , such as SQ. e extraction time reduces considerably; Krulj et al [90] found differences between the solvent and ScCO 2 method using petroleum ether for the squalene extraction from three amaranth genotypes.…”
Section: Methods Of Extraction Of Squalenementioning
confidence: 99%
“…Generally, ScCO 2 is a recommended technique for nonpolar compound extraction with molecular weights less than 500 g/mol soluble in CO 2 , such as SQ. e extraction time reduces considerably; Krulj et al [90] found differences between the solvent and ScCO 2 method using petroleum ether for the squalene extraction from three amaranth genotypes.…”
Section: Methods Of Extraction Of Squalenementioning
confidence: 99%
“…The variables are presented by vectors in factor space, while the correlation between two variables is indicated by the angle between vectors (the high correlation corresponds to small angle between vectors) (Krulj et al, 2016). Having this in mind, it can be observed that high positive correlation exists between AME and AOH content (r = 0.990, p < 0.001), and also the strong negative correlation to trade quality parameters VW and TKW.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 99%
“…The literature has compared three techniques, expeller pressing, organic solvent extraction, and supercritical fluid extraction (SCFE) showing that the best yield is achieved 69.5 g/kg by SCFE [18]. Other methods had been proved by Krulj et al [19] who extracted amaranth oil from raw seeds using accelerated solvent extraction and achieved higher yield than supercritical fluid extraction 78.1 and 61.1 g/kg, respectively. Relatively low temperature extraction results in almost no-thermal degradation of labile compounds.…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
“…As mentioned above, the most common presentation to commercialize amaranth is a puffed seeds; milling seeds would limit its commercialization, increasing steps in extraction process and rising production cost; however, it is possible to obtain oily extracts from nonmilled raw seeds, although with relatively low yields [19,22].…”
Section: Journal Of Food Qualitymentioning
confidence: 99%
See 1 more Smart Citation